Volatile constituents of Pinus roxburghii from Nepal - Satyal, Prabodh (Medknow Publications & Media Pvt Ltd, 2013)
BACKGROUND: Pinus roxburghii Sarg. Is one of 3 species of pine found in Nepal, the oil of which is traditionally used to treat cuts, wounds, boils, and blisters. OBJECTIVE: To obtain, analyze, and examine the anti-microbial and cytotoxic activities of the essential oils of P. roxburghii. MATERIALS AND METHODS: Three plant parts (cone, needle, and bark) of Pinus roxburghii were collected in Biratnagar, Nepal. The essential oils were obtained by hydrodistillation, and the chemical compositions were determined by GC-MS. The needle and cone essential oils were screened for anti-microbial activity against Bacillus cereus, Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli, and Aspergillus niger; brine shrimp (Artemia salina) lethality; and in-vitro cytotoxicity against MCF-7 cells. RESULTS: GC-MS analysis for the cone oil revealed 81 compounds with 78 components being identified (95.5% of the oil) while 98.3% of needle oil was identified to contain 68 components and 98.6% of the bark oil (38 components) was identified. The 3 essential oils were dominated by sesquiterpenes, particularly (E)-caryophyllene (26.8%-34.5%) and α-humulene (5.0%-7.3%) as well as monoterpene alcohols terpinen-4-ol (4.1%-30.1%) and α-terpineol(2.8%-5.0%). The monoterpene δ-3-carene was present only in needle and cone essential oils (2.3% and 6.8%, respectively). Bio-activity assays of the cone essential oil of P. roxburghii showed remarkable cytotoxic activity (100% killing of MCF-7 cells at 100 μg/mL) along with notable brine shrimp lethality (LC(50) =11.8 μg/mL). The cone essential oil did not show anti-bacterial activity, but it did exhibit anti-fungal activity against Aspergillus niger (MIC=39 μg/mL). CONCLUSION: The bioactivity of P. roxburghii essential oil is consistent with its traditional medicinal use.